2019
DOI: 10.5219/1109
|View full text |Cite
|
Sign up to set email alerts
|

Plants of Nepeta cataria var. citriodora Beck. and essential oils from them for food industry

Abstract: Nepeta cataria var. citriodora Beck. (catmints) is a source industrial production of citral and attractive raw material for food industry and cooking. Aerial part of Nepeta are characterized by high antimicrobial activity and fungicidal action against mold fungi, used in folk medicine, as ingredient in recipes for sausages, liqueurs and soft drinks, vegetable and fruit canned food, in the manufacture of vermouth. Ukrainian variety 'Melody' was created specifically for growing in the Forest-Steppe zone, and var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 24 publications
(2 reference statements)
0
10
0
1
Order By: Relevance
“…Indeed, essential oils have a lipophilic nature and high affinity for cell membranes. In this way, they could result in manifest changes in the polarization of cancer cell and particularly mitochondrial membranes along with ionic channels and disturbing membrane potential, thereby inhibiting proton pumps and ATP production (Lesgards et al, 2014;Frolova, et al, 2019). It was also reported that essential oils could disrupt the membrane ionic pumps and lead to ion (calcium) and membrane proteins leakage…”
Section: Cytotoxic Effect Of Saeomentioning
confidence: 99%
“…Indeed, essential oils have a lipophilic nature and high affinity for cell membranes. In this way, they could result in manifest changes in the polarization of cancer cell and particularly mitochondrial membranes along with ionic channels and disturbing membrane potential, thereby inhibiting proton pumps and ATP production (Lesgards et al, 2014;Frolova, et al, 2019). It was also reported that essential oils could disrupt the membrane ionic pumps and lead to ion (calcium) and membrane proteins leakage…”
Section: Cytotoxic Effect Of Saeomentioning
confidence: 99%
“…Nepeta cataria L., commonly known as catnip, is popular in the pet-toy industry, due to its effects on felines induced by the nepetalactones compounds. Besides this common use, Nepeta essential oil has multiple benefits in the treatment of fever, insomnia, and inflammation; it has sedative effect, antimicrobial, and antioxidant properties; and it can be used as a bioherbicide, insect repellant, preventive method for vector-borne diseases, growth inhibition and apoptosis of some cancer cells, and so on [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30]. Due to such properties, the essential oil demands have increased in the past years in food, pharmaceutical, and cosmetic industry, making them valuable products.…”
Section: Introductionmentioning
confidence: 99%
“…Essential oil of N. cataria is a colorless, mobile liquid with a pleasant herb-citrus aroma with tones of geraniums [75][76][77][78][79][80][81] . The main essential oil constituents of catmint were nepetalactones, geraniol and α-pinene, while nerol, citronellal, neral and caryophyllene oxide were the main constituents of lemon catnip 52,82 . Nepetalactones are a specific type of monoterpene known as iridoids.…”
Section: Microscopymentioning
confidence: 99%